2014
DOI: 10.3390/su6085187
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Living in Africa: Case of Water, Sanitation, Air Pollution and Energy

Abstract: Abstract:The study reviewed developmental challenges confronting African countries with specific reference to the availability of potable water, sanitation, energy, water and ambient air. It showed the conflict between the need to exploit environmental capital in order to keep up with the pace of human development activities and the need to utilize resources sustainably. Hitherto, the cost of this development has been at the expense of public health and cleaner environment. The outcome demonstrates the need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…While electricity from hydropower plant is widely acknowledged as environmentally friendly, those from fossil fuels and nuclear power have associated environmental limitations. This is because of the harmful effects of their by-products [1,2]. It is reported that energy production from fossil sources (both in the form of electricity and heating) is one of the major sources of anthropogenic emissions of CO2 and other greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While electricity from hydropower plant is widely acknowledged as environmentally friendly, those from fossil fuels and nuclear power have associated environmental limitations. This is because of the harmful effects of their by-products [1,2]. It is reported that energy production from fossil sources (both in the form of electricity and heating) is one of the major sources of anthropogenic emissions of CO2 and other greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%
“…While countries have started to look at ways of harnessing the abundant environmentally friendly renewable resources, some others have already proved it and are extending their generation capacities. China, United States, Germany, Spain, India are some examples of countries who have annual installed wind power capacities in the regions of some Giga-Watt (GW) of electricity [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…According to Omole and Ndambuki (2014), rapid population expansion, increase in the demand for fossil fuel consumption and uncontrolled extraction and industrial activities are the major causes of air pollution in Africa. However, a report by UNEP (2014), shows that in urban areas vehicular emissions remain the major cause of air pollution.…”
mentioning
confidence: 99%
“…In a quest to cushion the effects of human wants, lot of natural resources is required with most of these resources used for this purpose are not sustainable. Unfortunately, the daily activities of humans are hugely dependent on the natural resources available and their longevity somewhat proportionate to sustainable practice [16].…”
Section: Characteristics and Uses Of Nigeria Wind Energymentioning
confidence: 99%